The Presence and Roles of University Museums in Indonesia - Pungki Purnomo (Insaniyat : Journal of Islam and Humanities, 2022)
The study of museums in almost all leading universities in Indonesia continues to develop from time to time. This research aims to explore the arguments of the campus community about the founding factors and their opinions about the presence and roles of university museums. The Airlangga University History and Culture Museum and the UGM Mandala Majapahit Museum are the main references for this research. A phenomenological approach with in-depth interviews, observations and relevant literature studies is used in this study. Research findings reveal that several factors of the university museums presence are due to the initiatives from university leaders. University museums serve as historical reminders, fulfill educational and research needs, and instill the identity of campus communities. In relation to the role of university museums, the campus community believes that its role is similar to libraries in supporting learning and research activities and even as community service. Considering the importance of university museums, both university leaders and the education ministry authorities are required to provide optimal support, especially by providing official regulations to support the function of museums as part of information institutions at universities.